Methodical instructions for the implementation of practical tasks from the course "Project management in marketing" - Vasyltsova, Svitlana; Romanchyk, Tatyana (National Technical University "Kharkiv Polytechnic Institute", 2024)
The term "project" is not new for the domestic economy. It was customary to understand a project as a documented plan of a building (structure). In the English-language economic literature, this concept is usually referred to as "design". The transition to market relations has brought many new terms and concepts to economic life. The term "project" has also received a broader interpretation and its meaning has come closer to the English "project", which covers the entire process – from the emergence of an idea, its development, implementation to obtaining a result.
Keywords: methodical instructions; structuring marketing projects; analysis of the break-free project; risk management in the project; project planning; control